Factors Affecting Topical Treatment Success in Pediatric Scabies Cases: A Cross-Sectional Study - Muazzez Çiğdem Oba; Defne Özkoca; Rana Başara Şahin; Didem Şenses Kazan; Gaye Guldiken; Beril Kara Esen (Mattioli1885, 2023)
Introduction: Scabies is a common disease affecting the pediatric population. Treatment failure and relapses are frequent. Objectives: We aimed to define factors affecting topical treatment success in pediatric scabies patients. Methods: This multicenter cross-sectional study was performed between April and December 2022. Pediatric scabies cases were classified as treatment failure (TF) versus treatment success (TS). Results: We enrolled 170 patients in the study. In the TF group, the presence of symptomatic household members and referral from physicians other than dermatologists were more common (both p<0,001) and relapse rates and total symptom duration were higher (p=0,007, p<0,001 respectively). Permethrin 5% was more commonly used in the TF group (71.1% versus 25%) (p<0,001); however, the ratio of patients treated with sulfur preparations was significantly higher in the TS group (60.7% vs 16.9%) (p<0,001). Misapplication of topical therapy was significantly more common in the TF group (p<0,001), statistically significant errors being: (i) lack of treatment of close contacts (p<0,001); (ii) single application (p<0,001); and (iii) local application (p=0,027). In a multivariate analysis, treatment success was mainly associated with (i) presence of atopy (O.R.: 5,29, 95% CI:  1,22-25,57) ;(ii) absence of symptomatic household members (O.R.: 5,29, 95% CI:  1,72-16,27);  (iii) presentation to dermatologists rather than other specialties (O.R.: 6,08, 95% CI: 1,9-19,51); whereas use of permethrin negatively affected treatment success (O.R: 0,22, 95% CI: 0,07-0,71). Conclusions: Pediatric scabies patients should be treated before other family members get affected and with topicals other than permethrin. Awareness of scabies disease needs to be increased among non-dermatologists.